Reliability and failure analysis of solder joints in flip chip LEDs via thermal impedance characterisation. (September 2017) - Magnien, J.; Mitterhuber, L.; Rosc, J.; Schrank, F.; Hörth, S.; Goullon, L.; Hutter, M.; Defregger, S.; Kraker, E.
Abstract: Flip chip technology has made significant improvements to LED chip on board (COB) packages and modules by reducing thermal resistance compared with traditional wire bonded LEDs. However, one of the critical issues of flip chip packaged LEDs is the reliability of their solder interconnects, which are responsible for the heat transfer to the substrate. Based on a supply switching test, also called power cycle test, a model for monitoring and reliability was done to describe the remaining lifetime and additional the solder fatigue. Therefore, changes in thermal resistance of the LED-module were measured and correlated with solder fatigue of the LED flip chip package. Thermal impedance measurements were performed to monitor the status of the LED-module. Detailed analyses, comparing with the initial state, allow the evaluation of the occurring temperature swing of each LED chip. Single chip analysis combined with a thermal resistance driven monitoring model allows the calculation of remaining lifetime at each time during testing and beyond the first chip failure in a multi chip LED-module. Accordingly, it could be shown that the thermal impedance is a powerful tool for reliability monitoring and failure analysis. Highlights: Parametric monitoring model based on Rth to define remaining power-cycles until chip failure Thermal impedance analysis as online monitoring tool for lifetime prediction Failure root cause analysis via thermal impedance and radioscopic XR-CT analysis